2021
DOI: 10.1049/rpg2.12196
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic analysis of direct combustion and gasification systems for off‐grid energy supply: A case for organic rankine cycle and dual fluidized‐bed

Abstract: Biomass is one of the most versatile sustainable energy sources. This versatility allows utilization of different biomass feedstock using a verity of conversion techniques. Often, a biomass‐to‐bioenergy conversion method is selected depending on the application, end‐use product, and the type of feedstock. In many applications such as residential energy supply, it is possible to select amongst various technologies. Although, there exist several challenges such as cost‐effectiveness and sustainability that const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…To determine a biomass conversion plant's economic viability, techno-economic considerations must be taken into account. In addition to end product application and feedstock availability, challenges such as cost-competitiveness and sustainability constrain bioenergy development [95]. The cost of fluidized bed gasification varies depending on factors like the region of the world, the type of feedstock, the cost of supplies for conversion processes, the size of the production, and the length of the production process.…”
Section: Techno Economicsmentioning
confidence: 99%
“…To determine a biomass conversion plant's economic viability, techno-economic considerations must be taken into account. In addition to end product application and feedstock availability, challenges such as cost-competitiveness and sustainability constrain bioenergy development [95]. The cost of fluidized bed gasification varies depending on factors like the region of the world, the type of feedstock, the cost of supplies for conversion processes, the size of the production, and the length of the production process.…”
Section: Techno Economicsmentioning
confidence: 99%
“…Fermentation is central in biofuel production but is limited by feedstock type and often requires significant preprocessing [65]. When considering the Dominican Republic's unique context, with its distinct agricultural profile and logistical challenges, gasification and direct combustion stand out in [66]. Their adaptability to various waste types and scalability makes them apt for addressing the nation's energy needs using residual biomass.…”
Section: Critical Routes and Logistics Of Residual Biomassmentioning
confidence: 99%
“…With the autothermal gasifier design, it becomes possible to avoid the introduction of air into the GR, and it enables one to conduct pure steam or CO 2 gasification for high-quality syngas production. Bagherian et al showed that DFB is able to avoid bed material/biomass agglomeration by creating two separate reaction zones, thus improving the economics. Aghaalikhani et al demonstrated that efficient gas–solid contact and heat and mass transfer in DFB significantly benefit hydrogen production via biomass steam gasification.…”
Section: Introductionmentioning
confidence: 99%